Does habitat stability structure intraspecific genetic diversity? It's complicated... - Wieringa, Jamin G.; Boot, Matthew R.; Dantas-Queiroz, Marcos V. [UNESP]; Duckett, Drew; Fonseca, Emanuel M.; Glon, Heather; Hamilton, Natalie; Kong, Sungsik; Lanna, Flavia M.; Mattingly, Kali Z.; Parsons, Danielle J.; Smith, Megan L.; et al. (California Digital Library (CDL), 2020)
Regional phylogeographic studies have long been conducted in the southeastern United States for a variety of species. With some exceptions, many of these studies focus on single species or single clades of organisms, and those considering multiple species tend to focus on deep historical breaks causing differentiation. However, in many species more recent factors may be influencing genetic diversity. To understand the roles of historic and contemporary processes in structuring genetic diversity, we reanalyzed existing genetic data from Southeast of North America using approaches gleaned from phylogeographic and landscape genetic literature that were implemented across species including AMOVAs, PCoAs, Species Distribution Modelling, and tests of isolation by distance, environment, and habitat instability. Genetic variance was significantly partitioned by ecoregions, watersheds, and across phylogeographic breaks in the majority of species. Similarly, genetic variation was significantly associated with some combination of geographic or environmental distance or habitat instability in most species. Patterns of genetic variation were largely idiosyncratic across species. While habitat instability over time is significantly correlated with genetic diversity in some species, it appears generally less important than isolation by geographic or environmental distance. Our results suggest that many factors, both historical and contemporary, impact genetic diversity within a species, and more so, that these patterns aren't always similar in closely related species. This supports the importance of species-specific factors and cautions against assumptions that closely related species will respond to historical and contemporary forces in similar ways.
Keywords: Barriers; Comparative phylogeography; CpDNA; Data repurposing; MtDNA; Phylogeography; Pleistocene glaciation